Lung cancer patients with nephropathy as the first manifestation: Literature review and clinical study report - Qianqian Xu; Guming Zou; Li Zhuo; Hongmei Gao; Wenge Li (Frontiers in Oncology, 2022)
BackgroundTo investigate the relationship between membranous nephropathy (MN) and lung cancer.MethodsTo report patients with lung cancer detected by follow-up after the diagnosis of MN by renal biopsy in China-Japan Friendship Hospital from January 2010 to December 2019, and to study the prognosis of lung cancer-associated MN and have a review of the literature.ResultsLung cancer was detected in six patients followed for 1–27 months (median 8 months) after the diagnosis of MN: including four cases of lung adenocarcinoma, one case of carcinoma in situ, and one case of small cell lung cancer with multiple metastases. Five cases were in remission after surgical resection, and one case was remitted after chemotherapy. Six patients were negative for serum anti-PLA2R antibodies, and glomerular IgG subclass deposition detected by immunofluorescence was positive for IgG1 and IgG2. Glomerular PLA2R, THSD7A, and NELL-1 stainings were assessed in all six patients; one patient was positive for glomerular PLA2R staining, two patients were positive for glomerular THSD7A staining, and all patients were negative for NELL-1 staining. A literature review of the relationship between MN and lung cancer was performed: seven articles about cancer-associated MN were searched, reporting 32 cases of MN associated with lung cancer, among which 14 cases had nephropathy as the first manifestation and only five patients had remission of MN after treatment of lung cancer.ConclusionsA few lung cancer patients have nephropathy as the first clinical manifestation, and MN can also be remitted after treatment of lung cancer.